How Turkey's democratic backsliding compromises the international dimension of democratization. (15th December 2020) - San, Serdar; Akca, Davut
Abstract: Previous research suggests that linkage to the West can have a strong democratizing influence on transitioning states. Yet, Western linkage and leverage lost much of their democratizing force by the early twenty‐first century. Turkey's political trajectory over the last decade furnishes a representative case study of the waning power of the West as an anchor for democratization in high‐linkage countries. Despite Turkey's robust ties to the West, competitive authoritarianism has been further entrenched and signs of a drift toward full‐fledged authoritarianism emerged since the failed coup of July 2016. We argue that in a context where the European Union and the United States' willingness to support democracy declined considerably the AKP's distancing from the West in foreign policy and balancing the Western powers with its new economic and political relations with autocratic regimes have served to stifle the democratizing pressure of Western linkage by lowering the cost of autocratic behavior for the AKP government and facilitating Turkey's illiberal turn.